2006
DOI: 10.1002/eji.200535422
|View full text |Cite
|
Sign up to set email alerts
|

Surface expression of HSP72 by LPS‐stimulated neutrophils facilitates γδT cell‐mediated killing

Abstract: During inflammation and sepsis, accumulation of activated neutrophils causes lung tissue damage and organ failure. Effective clearance of neutrophils reduces the risk of organ failure; however, its mechanisms are poorly understood. Because lungs are rich in cdT cells, we investigated the physiological role of these cells in the protection of lung tissue from infiltrating neutrophils. In a mouse model of sepsis, we found that the lungs of survivors contained significantly higher numbers of cdT cells than those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 43 publications
3
44
1
1
Order By: Relevance
“…Hsp72 surface expression on stressed tumor cells also augments the cytotoxicity of NK cells (45). Recent reports provide evidence of the surface expression of Hsp90 on B cell lymphomas upon EBV infection (46), the expression of Hsp60 on stressed endothelial cells (47), and the expression of Hsp72 on neutrophils by LPS (48), suggesting the surface expression of Hsps under stressed conditions. Hsps can elicit immune responses if expressed on plasma membrane (35).…”
Section: Discussionmentioning
confidence: 99%
“…Hsp72 surface expression on stressed tumor cells also augments the cytotoxicity of NK cells (45). Recent reports provide evidence of the surface expression of Hsp90 on B cell lymphomas upon EBV infection (46), the expression of Hsp60 on stressed endothelial cells (47), and the expression of Hsp72 on neutrophils by LPS (48), suggesting the surface expression of Hsps under stressed conditions. Hsps can elicit immune responses if expressed on plasma membrane (35).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, apart from their potential role in regulating cell death, hsp have been implicated in the generation of immune responses [8,9]. Hsp have been shown as potent inducers of the innate immune system through interactions with cell surface receptors, leading to enhanced expression of pro-inflammatory cytokines [10,11], chemokines [12,13], and activation of dendritic cells (DC) [14][15][16] and other immune cell types [17][18][19]. In addition, through its peptide-and protein-binding properties, hsp have been demonstrated to act as strong adjuvants in the induction of adaptive immunity towards chaperoned molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, several recent studies have demonstrated that Hsp molecules can appear on the cell surface of normal and transformed cells (7,17,(21)(22)(23). The mechanisms by which Hsp molecules are translocated to and expressed on the cell surface are poorly understood.…”
Section: Hsp and Cellular Distressmentioning
confidence: 99%
“…In contrast to the well-defined roles of Hsp in the intracellular compartment, the functions of Hsp molecules on the cell surface of normal (28), infected (21), transformed (18,22), and apoptotic cells (23,24) (7,17,18,(29)(30)(31). Another function of Hsp may be to stabilize plasma membranes that are damaged by toxins and stress-related metabolites generated in response to infections or inflammation (32).…”
Section: Hsp and Cellular Distressmentioning
confidence: 99%
See 1 more Smart Citation